(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
Some hydrogeological and engineering geological problems that effectively might be solved with the help of proposed geophysical methods have been briefly discussed in the paper. In particular, such problems related to ground water prospecting and definition of its spatial distribution, investigations of infiltration processes of hydrotechnical constructions and problems of their safe operation, investigations of landslides, etc. Effectiveness of geophysical methods depends on proper selection of the assemblage of various methods, evaluation of impacts of physical and geological factors, as well as basing on interpretation of obtained field data.